(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
In criminal cases, proof is crucial, both theoretically, as it is the means of applying the penal code, and practically, as it necessitates uncovering the truth. This involves scrutinizing the initial doubt to determine whether the accused is the true perpetrator of the crime—and thus receives the appropriate punishment—or whether they are innocent. Hence, proof in criminal cases acquires its fundamental importance, as it leads to conviction or acquittal. Criminal proof strives to achieve this objective while upholding two fundamental principles: protecting the public interest and ensuring the punishment of every criminal, on the one hand, and protecting individual freedom and human dignity, on the other. This also includes guaranteeing that no innocent person is punished in any way. It can be said that there are general rules or provisions for proof in Islamic law, meaning those rules that apply to all crimes, whether they fall under the categories of Hudud (fixed punishments) and Qisas (retaliation) or Ta’zir (discretionary punishments). These rules consist of placing the burden of proof on the accused, establishing the principle of judicial conviction in general, and averting punishments based on mere suspicion, which some contemporary jurists extend to encompass all crimes, regardless of their category.